The effect of X-ray irradiation to the formation of polychromatic erythrocyte cell micronucleus in Wistar rats (Rattus norvegicus) - Eha Renwi Astuti; Hutojo Djajakusuma; Indeswati Diyatri; Nastiti Faradilla Ramadhani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Panoramic and cephalometric radiography is very important for diagnosis, treatment plan, and evaluation of orthodontic treatment results. Panoramic and cephalometric radiography are frequently performed at the same time, causing DNA damage and chromosome aberration. Purpose: This study aims to analyse the effect of X-ray exposure in panoramic and cephalometric radiography on micronuclei cell numbers. Methods: Laboratory-based analytical study with 60 healthy-male Wistar rats weighing 200–300 grams divided into 6 treatment groups (n=10). The control group: without radiographic exposure, the treatment group 2: using panoramic radiographic exposure followed by cephalometric, and the treatment group 3: using panoramic radiographic exposure and 24 hours later performed cephalometric radiographic. The unit of analysis was the polychromatic erythrocytes of mice cell, were examined 24 hours and 48 hours after irradiation had been finished. The polychromatic erythrocytes were examined using May-Gruenwald-Giemsa staining and 100x magnification under a microscope with 2000 cells per view. Data obtained were analysed using the SPSS 20 version software. The mean and standard deviations were calculated for each clinical parameter, and a one‐way ANOVA statistical test of significance was used. Statistical significance was set at p<0.05. Results: The analysis showed a significant increase (p<0.05) in the number of micronucleus in groups that used panoramic radiographic exposure followed by cephalometric. Conclusion: X-ray radiation can increase the number of micronucleus in polychromatic erythrocyte cells in rats.